ANALYZING TEACHERS’ ROLE IN SBDP LEARNING AT FIFTH GRADE OF ELEMENTARY SCHOOLS IN CLUSTER ONE KECAMATAN TAMPAN KOTA PEKANBARU - Hikmah Aulia Rizki; Zufriady; Guslinda (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This was a qualitative research aiming to describe the role of teachers in SBdP learning at the fifth grade of elementary schools in Cluster One, Kecamatan Tampan, Pekanbaru. The data were collected through observations, interviews, and documentation. The instruments used were observation sheets and interview guides referring to indicators of teachers’ roles in learning, and these instruments were validated by experts or validators. The subjects of this study were four fifth-grade teachers from elementary schools in Cluster One, Kecamatan Tampan. The findings showed that teachers performed their roles in SBdP learning well, although the implementation was not yet optimal. In the indicator of the teacher as a demonstrator, teachers presented SBdP materials both theoretically and practically. In the indicator of the teacher as a class manager, teachers conducted SBdP learning thematically and applied a scientific approach. Furthermore, in the indicator of the teacher as a mediator, teachers used pianics, pictures in student books, as well as audiovisual media such as the song “Gugur Bunga” and a video of the human circulatory system. In the indicator of the teacher as a facilitator, teachers utilized thematic printed books, worksheet books, and national compulsory song books as learning resources. Finally, in the indicator of the teacher as an evaluator, teachers had not yet implemented quizzes, portfolios, or project-based assessments, but they did carry out an assessment process.